The complete book of floorcloths design & techniques for painting great-looking canvas rugs - Cooper, Kathy (Lark Books, 1997)
With complete instructions for a score of techniques, and with ten complete projects, each shown in colour and featuring step-by-step drawings, this book shows you how to make colourful and useful floorcloths, that can be designed to fit any decor.